2020
DOI: 10.1002/adbi.202000003
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Enhanced Biosensing for Multiplexed Profiling of Extracellular Vesicles

Abstract: composition and molecular profiles of EVs in clinical samples. However, their unique sizes (50-1000 nm) impose technical challenges in conventional analytical methods, which often lead to variable findings. Conventional methods for protein analyses (e.g., western blotting, enzymelinked immunosorbent assay) require large amounts of samples and involve time-consuming and extensive processing steps, making them impractical in the clinical settings. Developing new EV molecular profiling platforms is, thus, a pivot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…Min et al used a method they reported previously, nanoplasmonic exosome (nPLEX) [ 39 ], for multiplexed detection of surface biomarkers via fluorescently-labeled antibodies [ 105 ]. The antibodies are captured on a surface with gold nanoholes to enable plasmon-enhancement of the fluorescence.…”
Section: Advances In Methods For Single Ev Analysismentioning
confidence: 99%
“…Min et al used a method they reported previously, nanoplasmonic exosome (nPLEX) [ 39 ], for multiplexed detection of surface biomarkers via fluorescently-labeled antibodies [ 105 ]. The antibodies are captured on a surface with gold nanoholes to enable plasmon-enhancement of the fluorescence.…”
Section: Advances In Methods For Single Ev Analysismentioning
confidence: 99%
“…The labeled EVs are imaged, and their fluorescent intensities are analyzed. Therefore, biomarker distribution analysis could be performed on a single-EV level [25]. A localized surface plasmon resonance imaging (LSPRi) platform improves the limit of detection down to the single exosome limit.…”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%
“…In another recent study, Min et al explored long-range (> 100 nm) SPR-enhanced fluorescence on a periodic array instead of the localized "hotspot" surfaces (< 20 nm). This approach is more suitable for measurements with intact EVs given their dimension (30-1000 nm) [118,119]. Four fluorescent dyes (AF488, Cy3, Cy5, and Cy5.5) were conjugated with streptavidin separately in order to code biotinylated EV membrane proteins (CD9, CD63, CD81, GAPDH, EGFR, EGFRvIII) after their capture on neutravidin-PEG layers (Fig.…”
Section: Spr Arraysmentioning
confidence: 99%
“…In summary, the binding events of EV components to the sensing interface can be monitored by surface sensitive techniques such as SPR in a label-free format or by labelling them with one or multiple reporters, i.e. using a combination of physico-chemical coding strategies [118]. The advanced nano-/micro-fabrication-assisted SPR arrays and their integration into microfluidic chambers have been increasingly employed to facilitate better sample manipulation and miniaturization.…”
Section: Spr Arraysmentioning
confidence: 99%